Repair of Combined Cheek and Nose Defects: Categorization and Utilization - Hamilton, Kristy L.; Weathers, William M.; Wolfswinkel, Erik M.; Thornton, James F. (Seminars in Plastic Surgery, 2013)
Combined cheek and nose soft tissue defects can represent a formidable challenge to the reconstructive surgeon. It is important for the surgeon to think of these defects as four separate categories: cheek with nasal sidewall, cheek with nasal sidewall and exposed bone, cheek with nasal sidewall plus ala, and cheek with simple posterior ala defect. This categorization will help the surgeon plan the repair and provide a successful aesthetic outcome. There are multiple repair options that the surgeon can use, and the surgeon should be facile with all types. It is universally agreed that the cheek defect must be repaired prior to undertaking the repair of the nasal defect.
Keywords: combined cheek and nose defect; forehead flap; Shark Island pedicle flap; full-thickness skin graft